2019
DOI: 10.25120/etropic.18.2.2019.3707
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Gothic: Frankenstein, Art and the Microplastic Monster

Abstract: The contamination of life with plastic pollution and humanity’s lethargic response to the problem is an unfolding terror: a story of Gothic horror unfolding in contemporary times. The power of Mary Shelley’s Gothic novel Frankenstein looms over the current terror of plastic pollution to encourage changes to the materials we create, use and discard. In Frankenstein, a monster was spawned in a process that desecrates the act of creating new life. Similarly, in my work of art Microplastics Found in Human Embryo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…In vitro studies on human cells have shown that MP fibers can irritate the lungs and destroy alveolar cells (Goodman et al ., 2021). Nanometer-sized MPs can even cross the blood–brain barrier and placenta and cause changes in endogenous metabolites and gut microbial communities (Glade-Wright, 2019). In a recent study, new technology was used to measure plastic particles ≥700 nm in the blood samples from 22 healthy humans and the mean of the sum quantifiable concentration was 1.6 μg ml −1 (Leslie et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies on human cells have shown that MP fibers can irritate the lungs and destroy alveolar cells (Goodman et al ., 2021). Nanometer-sized MPs can even cross the blood–brain barrier and placenta and cause changes in endogenous metabolites and gut microbial communities (Glade-Wright, 2019). In a recent study, new technology was used to measure plastic particles ≥700 nm in the blood samples from 22 healthy humans and the mean of the sum quantifiable concentration was 1.6 μg ml −1 (Leslie et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%